Factors Affecting Hypertensive Patients in Making Efforts to Prevent Complications in the Work Area of Tlogosari Wetan and Tlogosari Kulon Health Centers, Semarang City - Petro Dwi Siswanto; Bagoes Widjanarko; Martini Martini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the factors that influence hypertensive patients in making efforts to prevent complications in the working area of the Tlogosari Wetan and Tlogosari Kulon Public Health Centers, Semarang City. The types and designs in this research include quantitative research designs and survey research types. Survey research is a research that looks for how a health phenomenon occurs. The results showed that statistical analysis using the Chi square test with sig.0.05 showed the results of p value 0.007 meaning p <0.05 so ho was rejected, so it was concluded that there was a relationship between self-efficacy and efforts to prevent hypertension patients from getting complications in the work area. Tlogosari Wetan and Tlogosari Kulon Public Health Centers, Semarang City, as well as the results of statistical analysis using the Chi square test with sig.0.05 shows p value 0.303 meaning p>0.05 so ho is accepted, so it can be concluded that there is no relationship between effectiveness response and patient prevention efforts. Hypertension so as not to get complications in the working area of the Tlogosari Wetan and Tlogosari Kulon Health Centers, Semarang City